Pengaruh Pendapatan Dan Perilaku Keuangan Serta Locus Of Control Terhadap Literasi Keuangan Melalui Keputusan Berinvestasi Sebagai Variabel Intervening - Serli Rusli; Irfan Zam Zam; Rusman Soleman (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The purposes of this study are: (1) To analyze wheter income effects financial literacy and (2) To analyze wheter financial behavior effects financial literasi and (3) To Analyze wheter locus of control effects financial literacy and (4) to analyze wheter investment decision can mediate income, financial behavior and locus of control on financial literacy. The object of this reseach is micro, small and medium enterprices registered at the cooperatives and UMKM service in the city of Ternate. This type of reseach is quantitative. The analysis model in this study is multiple linear regression analysis using SPSS. Based on the result of this study indicate, (1) income has an effect on financial literacy, (2) Financial Behavior has a direct effect on financial literacy (3) Locus Of Control has a direct effect on financial literasi (4) Investment decisions cannot mediate the effect of income, financia behavior and locus of control on financial literasi.